THE IMPROVEMENT OF BASIC MEASUREMENT SKILLS THROUGH PAIR CHECK TYPE COOPERATIVE LEARNING MODELS - Windra Irdianto; Eko Edi Poerwanto; M. Ihwanudin (Universitas Negeri Malang, 2018)
Abstract: The Improvement of Basic Measurement Skills Through Pair Check Type Cooperative Learning Models. Pair check cooperative learning is a learning model of a small group of two students who are responsible for completing academic assignments with peer guidance. This study aims to explore the effect of cooperative learning pair check models on automotive measurement subject matter. Thirty-two students were divided into two groups. One group consisting of 17 students is an experimental class, while the other group consisting of 15 students is a control class. Research data is a score of students' skills in reading the results of automotive measurements. Research data was obtained at the final evaluation of learning using a questionnaire. The results showed that the average score of the experimental class was 78.35, while the average score of the control class was 57.73. The difference in the average score of the two groups was tested using t test statistics for independent groups. The results showed that the average score of the experimental group was significantly higher than that of the control group. This shows that cooperative learning type pair check can improve students' skills in reading the results of automotive measurements.